Optimized Guard Band Allocation for TN and NTN Coexistence Using Reinforcement Learning - Jang, Jiseok; Jung, Soyi (International Conference on ICT Convergence, 2024)
Efficient interference management is crucial for the coexistence of terrestrial networks and non-terrestrial networks. This paper proposes an approach to optimize frequency band allocation by determining the optimal guard bandwidth, reducing interference, and improving coexistence between terrestrial networks and non-terrestrial networks. Simulation results offer guidelines for setting appropriate guard bandwidth, ensuring effective terrestrial networks and non-terrestrial networks coexistence.
Keywords: Band allocation; Coexistence; Guard bandwidth; Guard-band; Interference management; Management IS; Non-terrestrial network; Reinforcement learnings; Terrestrial networks; coexistence; deep reinforcement learning; guard band; Non-terrestrial networks; terrestrial networks